Rozwój i zmiany klimatu w polityce zewnętrznej UE na przykładzie Afryki - Zajączkowski, Kamil (Rocznik Integracji Europejskiej, 2015)
The aim of this paper is to present and describe the EU’s policy with regard to environmental protection and countering climate change in Africa, in the context of the broader objective of reducing, or eliminating poverty. It is increasingly accepted that we need an integrated approach to climate change and development; only by linking these issues together can we show the entire complexity of the multidimensional issue of poverty. Global development requires taking into account issues related to susceptibility and adjustment to climate change. The paper seeks to answer the questions of the extent to which climate change is a serious and lasting threat to devel- opment, and about the relations between climate change and development. It presents the role and significance of climate change and environmental protection in EU development policy; it describes the major relevant documents and decisions. The author focuses particularly on discussing the issues of climate change and development in the relations between the EU and Africa, and points out the key challenge related to the implementation of policies combining climate and development. Although there is a general conviction about, and awareness of the interrelation of these two phenomena (processes), still too few of the necessary actions are being taken, and the activities related to development and climate are often approached and executed separately.